Investigating the Potential of Mushroom-Derived Polysaccharides as Adjuvants for COVID-19 Vaccines - Parinita Tripathy; Sambhavi Awasthi; Kanchan Yadav Arya; Sanyogita Shahi (The Bioscan, 2024)
Emphasis should be on vaccines that produce healthy robust immunity in the long run, especially against new strains. A good vaccine produces a strong and long-duration immune response. This includes adjuvants, which improve the immune response to vaccines, resulting in higher efficacy. Natural products, especially polysaccharides of medicinal mushrooms, have been ongoing work as new adjuvants for vaccines. These include the activation of innate immune cells such as macrophages, dendritic cells, and natural killer cells by the immunomodulatory properties of these polysaccharides, mostly β-glucans; cytokine induction; and augmentation of humoral as well as cellular immune responses. The present review discusses the possible role of polysaccharides derived from mushrooms as adjuvants in a COVID-19 vaccine. It covers the mechanisms of action, preclinical evidence from viral vaccine models, and the challenges associated with the incorporation of these natural compounds into COVID-19 vaccine platforms. The field shows very promising results in enhancing immunity in preclinical studies, but challenges like standardization and dosing, which turn into regulatory hurdles, are waiting in the wings. In summary, mushroom polysaccharides are promising adjuvants to be used to enhance vaccine efficacy, particularly in vulnerable populations, and concerning emerging variants of SARS-CoV-2. Further study will be necessary to establish their utility within COVID-19 vaccines and to determine how best they should be incorporated into the existing technologies that make up the vaccine formulations. The naturally occurring molecules could be a safer substitute for the enhancement of long-term immunity and provide greater access to vaccines globally.